Optimal planning on-grid power system for 2200VA household sector by considering economic criteria - Bandiyah Sri Aprillia; Kevin Octavianov Abdurohman (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
This study discusses efforts to model solar grid systems by considering economic and regulatory factors in system design. The Hybrid Optimization of Multiple Electric Renewables software is used to evaluate the economic viability of the on-grid PV technology that provides 2200VA of power in the household sector. Optimal costs are assessed from Net Present Cost (NPC) which is a cost analysis to determine investment feasibility based on interest rates and fees in the coming years and Break Even Point (BEP) which is the point where expenditure and income are balanced. The simulation results show that in the project period of 25 years the installation of on grid PV power system has an NPC that is 20% lower than the PLN network power supply with a BEP value lower than 15 years. The lowest NPC and BEP values were obtained from the installation of 7 PV panels with 300Wp capacity connected to the PLN network. This system is able to save electricity costs by IDR 23,060,260 compared to the use of 100% electricity from the State Electricity Enterprise grid. This system is worthy of being an economic tool for providing electricity services throughout the year and meeting rising energy demands in the household sector.